Anaxagoras on the Milky Way and Lunar Eclipses - Couprie, Dirk (Hyperboreus, 2018)
Anaxagoras is commonly known as the discoverer of the true explanation of eclipses of the moon as caused by the earth’s shadow. Anaxagoras is also said to have explained the phenomenon of the Milky Way as caused by the earth’s shadow. In this paper, the two theories are described, it is shown that and why they are incompatible, and it is argued which of the two most likely can be ascribed to Anaxagoras. This is ﬁrst studied by exploring which of the two theories is best documented. After that, it is examined which of the two ﬁts best with Anaxagoras’ other astronomical ideas. It is argued that both procedures point to the theory of the Milky Way as Anaxagoras’ actual conception of the role of the earth’s shadow. Consequently, the earth’s shadow has nothing to do with lunar eclipses, and Anaxagoras is mistakenly honored as the discoverer of the true theory of lunar eclipses. It is also argued that invisible heavenly objects that move before the moon, which are mentioned in the doxography on Anaxagoras as an additional explanation, must have been his one and only explanation of lunar eclipses, and it is tried to explain how this theory has come to be called additional. Finally, the unanswered question of Anaxagoras’ conception of the moon’s light and phases points forward to a sequel of this paper.